Identifikasi Aves di Kawasan Taman Nasional Gunung Merbabu Sebagai Bahan Pembuatan Multimedia Interaktif Biologi SMA - Dhesti Nurul Fadhillah (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
The purpose of this study is To determine the types of Birds (Aves) which can be used for the preparation of the learning media in the form of Interactive Multimedia Area of the National Park of Merbabu Mountain, Selo district, Boyolali Regency, The form of this research is RnD interactive multimedia, research Methods using point count method by applying random sampling in the taking of the shooting point. Data collection with the point count through the 4 replications. Large population is the entire Aves in the Area of Merbabu Mountain National Park.Results and conclusion the types of Aves found in the Area of Merbabu Mountain National Park as many as 12 Family 17 species and 156 individuals.Assessment of the third expert stated that the learning media in the form of interactive multimedia is Very Feasible to used as media of learning are valid. The application of learning media in the classroom by utilizing interactive multimedia as a teaching material at the time of learning according to the material or KD that have been written on the syllabus. Keywords: identification aves, interactive multimedia, merbabu mountain national park.